NANOGrav detects the gravitational-wave background - Coelho, Jaziel Goulart; Marra, Valerio; Pereira, Jonas P. (Cadernos de Astronomia, 2023)
Professors from Núcleo Cosmo-ufes comment on the recent result of the NanoGrav collaboration, which detected a background of gravitational waves in the universe.